How can Californians be overweight and hungry? - Patricia Crawford; Marilyn Townsend; Diane Metz; Dorothy Smith; Gloria Espinosa-Hall; Susan Donohue; Anna Olivares; Lucia Kaiser (California Agriculture, 2004)
The United States is experiencing an epidemic of obesity in both adults and children, particularly among low-income populations. In fact, overweight has replaced malnutrition as the most prevalent nutritional problem among the poor. We examine this seemingly paradoxical relationship and explore the causes and consequences of overweight, obesity and food insecurity. In a UC Cooperative Extension Body Weight and Health Workgroup study of 561 low-income Latino mothers and their young children, we found important differences in the association between family food insecurity and overweight status for mothers and their children. Forty percent of the women were overweight and 37% obese, and 22% of their children were overweight. Furthermore, U.S.-born mothers who were food insecure as children were more likely to be obese adults. Awareness and understanding of the link between food insecurity and weight gain will facilitate the efforts of schools, food assistance programs, the food industry and others in the community to provide effective nutritional programs.